2013
DOI: 10.1099/jmm.0.055210-0
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis with the icaA− /icaD− /IS256 − genotype and protein or protein/extracellular-DNA biofilm is frequent in ocular infections

Abstract: In ocular infections (OIs) caused by Staphylococcus epidermidis, biofilms composed mainly of poly-N-acetylglucosamine (PNAG) have been widely studied, but PNAG-independent biofilms have not. Therefore, we searched for a relationship between the ica operon (involved in PNAGbiofilm) and the biochemical composition of biofilms in isolates from OI. Isolates from OI (n562), from healthy conjunctiva (HC; n545) and from healthy skin (HS; n553), were used to detect icaA and icaD genes, and the insertion sequence 256 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 41 publications
(48 reference statements)
1
17
0
Order By: Relevance
“…In fact, the benefits of PIA/PNAG to survival appear to have resulted in its ubiquitous production by a wide variety of pathogens [22]. It is clear however, that it is not always necessary for survival during infection as PIA/PNAG-negative S. aureus and S. epidermidis strains have been isolated [23], [24]. In S. epidermidis , and in a minority of S. aureus strains, PIA/PNAG production can be switched off by the insertion of an IS256 element in the icaC gene, however, prior to this study, phase variation of PIA/PNAG expression in S. aureus isolates that lack this insertion element was not clear [25], [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the benefits of PIA/PNAG to survival appear to have resulted in its ubiquitous production by a wide variety of pathogens [22]. It is clear however, that it is not always necessary for survival during infection as PIA/PNAG-negative S. aureus and S. epidermidis strains have been isolated [23], [24]. In S. epidermidis , and in a minority of S. aureus strains, PIA/PNAG production can be switched off by the insertion of an IS256 element in the icaC gene, however, prior to this study, phase variation of PIA/PNAG expression in S. aureus isolates that lack this insertion element was not clear [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite the metabolic cost, selection pressures that favor the PIA/PNAG-negative phase variants are likely less pronounced in vivo. However, skin colonization and ocular infections appear to favor the PIA/PNAG-negative phenotype in S. epidermidis and ica -negative clinical isolates of S. aureus have been detected as well [23], [24], [28]. Furthermore, as PCR amplification of the ica genes is often used to demonstrate the capacity to produce PIA/PNAG [29], [30], our finding that a 4-nt indel mutation can shut off PIA/PNAG production suggests that PIA/PNAG negative clinical isolates may be more prevalent than previously appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most of the isolates included in the present study were positive for at least one biofilm-related gene, especially aap and bhp, both associated with protein-related mechanism of biofilm maturation. The fact that both the ica locus and IS256 insertion sequence are infrequent among isolates included in the present study, as well as among ocular isolates independently studied (37), reinforces the idea that S. epidermidis isolates recovered from ocular tissues are not subjected to a selective pressure for strong biofilm formation, since maturation via intercellular protein adhesins results in weaker biofilms compared to PIA-dependent mechanisms (7). However, since the number of isolates recovered from endophthalmitis in the present study was small, this conclusion could be true for keratitis-associated strains only.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that ica-negative isolates were also predominant among S. epidermidis recovered from ocular tissues of patients suffering with distinct ocular infections in Mexico (37). Carriage of the ica locus by S. epidermidis implicates a fitness cost, and isolates lacking ica genes are able to outcompete strains carrying this locus (38).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the pathogenesis of S. epidermidis is linked to its presence as a normal flora on the human skin and the ability to adhere to biomedical materials and produce biofilm [18]. These sticky agglomerations enable S. epidermidis to inhibit most host defense mechanism and it is implicated in multiple antibiotic resistance [6,19]. This can justify the 91.3% methicillin resistance observed among the biofilm-producing S. epidermidis strains having the icaA gene.…”
Section: Discussionmentioning
confidence: 99%